Singapore negotiating state and society, 1965-2015 - Lim, Jason 1971-; Lee, Terence 1972- (Routledge Taylor & Francis Group, 2016)
"Critically reflects on 50 years of independence. Contributors interrogate a selected range of topics on Singapore's history, culture and society--including the constitution, education, religion and race--and thereby facilitate a better understanding of Singapore's shared national past. Central to this book is an examination of how Singaporeans have learnt to adapt and change in the face of policies introduced by the PAP government since independence in 1965. All chapters begin their histories from that point in time, and each contribution focuses either on an area that has been neglected in Singapore's modern history or offers new perspectives on the past. Using a multi-disciplinary approach, this book presents an independent and critical take on Singapore's post-1965 history".